055 Comparison of distributions of common indicators of socio-economic position by ethnicity and migration: preliminary findings from the Born in Bradford Birth Cohort Study. (16th November 2010) - Fairley, L; Small, N; Lawlor, D A; Wright, J
Abstract : Objective: To describe and compare the distributions, including extent of missing data, in measures of socio-economic position (SEP) between women of white British and Pakistani ethnicity. We also compare distributions of measures of SEP between Pakistani women born in UK and those born in Pakistan and also compare distributions by the woman's age at migration to the UK. Design: The Born in Bradford birth cohort study recruits pregnant women at 26–28 weeks gestation when they complete a baseline questionnaire; approximately half these women are of Pakistani origin. Setting: Bradford, UK. Participants: Data are currently available for 2005 White British and 2444 Pakistani women. Main outcome measure: Indicators of SEP included in these analyses are: the woman's education and employment, her partner's education and employment and household income. Results: 57% of the Pakistani ethnicity women were born in Pakistan and there was a bimodal distribution of age at migration to the UK with peaks at ages 1 and 18 years. 92% of the White British women were, or had been, in paid employment compared to 51% of the Pakistani women. This figure was 82% for UK-born Pakistani women, 73% for those born in Pakistan who moved aged 5 or under and 22% for those who moved after the age of 5. Overall 23% of women reported that they didn't know their family income; this varied by ethnicity and country of birth (8% for White British women, 21% for UK-born Pakistani women and 49% for those born in Pakistan). The percentage of women reporting an income of less than £20 000 was highest in Pakistani women, while the percentage of women reporting an income of £20 000 and over was highest for the White British women. 11% of White British women had no educational qualifications compared to 22% of Pakistani women; this figure was lowest for UK-born Pakistani women. The percentage of women with degree level education was higher in Pakistani than White British women (26% and 19%, respectively) and was similar for all Pakistani women irrespective of migration history. The percentage of women's partners with no qualifications was similar between ethnic groups, however the percentage of partners with degree level education was higher for the Pakistani women. Conclusion: These differences in the distributions of SEP measures by ethnicity and migration are important to understand health inequalities and for ensuring appropriate adjustment of SEP confounding.